Implementation of Diversion in Methamphetamine-Type Drug Crimes by Children - Ayu Lailatul Hajar; Galih Puji Mulyono; Teguh Suratman; Andri Sutrisno (Faculty of Law, University of Merdeka Malang, 2024)
This study examines various prevention efforts and efforts to overcome narcotics type metamfetamine in children by implementing diversion. The problems studied are related to the realm of the police in providing diversion to children who commit the crime. What challenges are faced by the police in providing diversion as an effort to overcome narcotics among children. This study uses an empirical research type with a juridical-sociological approach to see the role of the police in providing diversion to children who commit narcotics crimes. The types of data used are primary data and secondary data. Data collection techniques use interviews and document studies with selected quality data that is relevant to the problems raised. Data analysis used qualitative descriptive analysis. Based on the results of the analysis, the policeâ€™s considerations in providing diversion to children because they see external and internal factors from the child. The role of the police is very important to help handle children in conflict with the law, the police in carrying out their duties are partly successful and partly not in resolving the problem of narcotics crimes in children by implementing the principle of diversion.How to cite item: Hajar, A., Mulyono, G., Suratman, T., & Sutrisno, A. â€œF Implementation of Diversion in Methamphetamine-Type Drug Crimes by Children.â€ Jurnal Cakrawala Hukum 15 no. 1 (2024): 37-48. DOI: 10.26905/idjch.v15i1.14277.